Literature Study: Probing Prompting Model on Social Science in Elementary School - Dian islami; Vanda Rezania (Indonesian Journal of Islamic Studies, 2018)
This literature research aims to examine the application of Probing Prompting models to student’s critical thinking abilities in Social Sciences (IPS) subject in elementary schools. The Probing Prompting learning model is a learning that presents a series of questions that guide and explore student’s ideas so as to improve the thought process that is able to associate sudent’s knowledge and experience with new knowledge being learned. This model is applied to social science subjects. Social science is a science that examines various social and humanities disciplines as well as basic human activities. This research uses a method of literature study that describes some of the results of limited research, journals,books and asticles. The result of the literature study obtained are probing prompting model is able to influence both the learning results and the development of the mindset of students